Sliding On and Off of a Logarithmic Surface

In the x y z xyz -coordinate system, there is a surface parametrized in the following way: x 1 y = ln ( x ) z + . \begin{aligned} x &\geq 1 \\ y &= \ln(x) \\ -\infty \leq z &\leq + \infty. \end{aligned} A massive bead slides without energy losses on the bottom of the surface. Here, "bottom" means that the outward surface normal vector generally points towards the y -y direction. The bead can be modeled as a point-particle.

The bead is not strictly confined to the surface, and will either slide along the surface or leave the surface as physical conditions dictate. There is an ambient gravitational acceleration of 10 m/s 2 10\text{ m/s}^2 in the y -y direction.

Initially, the bead is located at ( x , y , z ) = ( 1 , 0 , 0 ) (x,y,z) = (1,0,0) (meters), and has a speed of 10 m/s . 10\text{ m/s}. At this time, the bead's velocity has no z z -component, and is tangential to the surface's cross-section in the x y xy -plane. The initial velocity is such that the bead's y y -coordinate is increasing.

What is the bead's x x -coordinate at the instant at which it leaves the surface?

Note: ln ( x ) \ln(x) denotes the natural logarithm of x . x.


The answer is 2.6547.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jan 17, 2018

There is no motion in the z z -direction. the position vector of the particle can be given by r = ( x ln x ) \mathbf{r} \; = \; \binom{x}{\ln x} and hence r ˙ = ( 1 x 1 ) x ˙ r ¨ = ( 1 x 1 ) x ¨ + ( 0 x 2 ) x ˙ 2 \dot{\mathbf{r}} \; = \; \binom{1}{x^{-1}}\dot{x} \hspace{2cm} \ddot{\mathrm{r}} \; = \; \binom{1}{x^{-1}}\ddot{x} + \binom{0}{-x^{-2}}\dot{x}^2 The particle is subject to gravity and (while in contact with the surface) a normal reaction N \mathbf{N} perpendicular to r ˙ \dot{\mathbf{r}} , and hence parallel to ( x 1 1 ) \binom{x^{-1}}{-1} . If we write N = m K ( x 1 1 ) \mathbf{N} = mK\binom{x^{-1}}{-1} , the equation of motion of the particle is m r ¨ = m g ( 0 1 ) + m K ( x 1 1 ) m\ddot{\mathbf{r}} \; = \; mg\binom{0}{-1} + mK\binom{x^{-1}}{-1} Thus r ¨ ( 1 x 1 ) = g x 1 ( 1 + x 2 ) x ¨ x 3 x ˙ 2 + g x 1 = 0 d d x [ 1 2 ( 1 + x 2 ) x ˙ 2 + g ln x ] = 0 \begin{aligned} \ddot{\mathbf{r}} \cdot \binom{1}{x^{-1}} & = \; -gx^{-1} \\ (1 + x^{-2})\ddot{x} - x^{-3}\dot{x}^2 + gx^{-1} & = \; 0 \\ \frac{d}{dx}\left[\tfrac12(1 + x^{-2})\dot{x}^2 + g\ln x\right] & = \; 0 \end{aligned} Given the initial conditions of this problem, we deduce that 1 2 ( 1 + x 2 ) x ˙ 2 + g ln x = 50 x ˙ 2 = 20 ( 5 ln x ) 1 + x 2 \begin{aligned} \tfrac12(1 + x^{-2})\dot{x}^2 + g\ln x & = \; 50 \\ \dot{x}^2 & = \; \frac{20(5 - \ln x)}{1 + x^{-2}} \end{aligned} Moreover, r ¨ ( x 1 1 ) = g + ( 1 + x 2 ) X ( 1 + x 2 ) X = x 2 x ˙ 2 g = 10 x 2 + 1 ( 9 2 ln x x 2 ) \begin{aligned} \ddot{r} \cdot \binom{x^{-1}}{-1} & = \; g + (1 + x^{-2})X \\ (1 + x^{-2})X & = \; x^{-2}\dot{x}^2 - g \; = \; \frac{10}{x^2 + 1}\big(9 - 2\ln x - x^2\big) \end{aligned} and so the particle first leaves the surface when 9 2 ln x x 2 = 0 9 - 2\ln x - x^2 = 0 , which happens when x = 2.65468 x = \boxed{2.65468} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...